A Study On Recruitment And Selection Process Towards Bix It Academy - et. al., Mrs. Sunitha. V, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The project title “A study on Recruitment and Selection Process” conducted in Bix IT Academy aims to find out the general opinion of the Recruitment and Selection process attended by the employees at Bix IT Academy. The main objective of the project is to study the process of Recruitment & Selection in Bix IT Academy. This study helps to make a decision in selecting the right candidates for the right job, this study helps the organization to identify the area of problem and suggest ways to improve the recruitment and selection process, this study helps to evaluate the time constraint for the recruitment process. Most of the employees were satisfied but changes are required consistent with the changing scenario as recruitment process features a great impact on the working of the corporate as a fresh blood, new idea enters within the company.